Inelastic housing supply: A friction of inter-regional migration - He, Siyuan. (2018)
Abstract: Inter-regional migration is supposed to be driven by income inequality and usually viewed as the primary mechanism by which the U.S. labor market adjusts to the income disparity across regions. However, the migration mechanism has failed to equalize the income disparity in the last thirty-five years. This paper investigates the role of housing supply on inter-regional migration based on MSA level data. The regression results show that the housing supply constraints will stimulate the response in housing price growth but mitigate the response in population growth to employment shock. The slower population growth in lower elastic MSAs could be partially explained by their less responses to labor demand shock in employment. And I find that positive labor demand shocks increase population or employment through mitigating out-migrations, rather than absorb more in-migrations. However, the housing supply constraints accelerate the out-migrations, slow down the income convergence rate across MSAs and even exacerbate the regional income inequality in the last thirty-five years. Further, the friction of inter-regional migration leads to a significant difference in demographic structure between two groups. MSAs with higher housing supply elasticities seemed to provide more opportunities to young people. However, housing supply constraints block up the redistribution of developing fruits to outsiders and capitalize more income into local housing values.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Economics.; Advisor: Marcelo Bianconi.; Committee: Jeffery Zabel, and Gilbert Metcalf.; Keyword: Economics.